The influence of substrate temperature on the optical and micro structural properties of cerium oxide thin films deposited by RF sputtering. (September 2015) - Murugan, R.; Vijayaprasath, G.; Ravi, G.
Highlights: CeO2 thin films deposited by using RF Magnetron sputtering with various substrate temperatures. The XRD analyses revealed that the deposited thin films have cubic structure. Deposited films have good transparency in the visible range. Photoluminescence and micro-Raman spectra were interpreted for CeO2 thin films. XPS studies confirmed CeO2 present in the deposited films (with different Ce3d states). Abstract: In this investigation, CeO2 thin films were deposited on glass substrates with different substrate temperatures by using RF Magnetron sputtering technique. The deposited films were characterized by X-ray diffraction (XRD), UV–visible spectroscopy, room temperature photoluminescence spectroscopy, micro-Raman and X-ray photoelectron spectroscopy. The thicknesses of the film were determined by using profilometer and it was varied from 0.70 μm to 0.87 μm. From the XRD results, it is evident that the film deposited at room temperature (RT) is amorphous in nature. The remarkable change in character from amorphous to crystalline is observed by increasing the substrate temperature from RT to 300 °C, and the crystallites were found to be in cubic phase with preferred orientation along (2 2 0). Calculated crystallite sizes were in the range of ∼8.6 nm. Optical characteristics were studied as a function of change in substrate temperature and thickness in air. Overall transmittance percentages of the films (85–60%) were found to decrease with increase in substrate temperatures. The results show that the energy band gap was found to be decreased (3.95–3.75 eV) with the increase of substrate temperature as well as thickness of the film. Optical constants like refractive index ( n ), extinction coefficient ( k ), optical conductivity ( σ ), real and imaginary part of dielectric constant ( ε 1 & ε 2 ), volume energy loss function (VELF) and surface energy loss function (SELF) were evaluated by using UV spectra. It is found from PL spectra that the decreased defects for the films prepared at a higher substrate temperature. A strong near band edge emission and weak green emission were observed at ∼360 and ∼519 nm respectively. The micro-Raman results show the characteristic peak of CeO2 F 2g at ∼465 cm −1 . It is found from the spectrum that the peak intensity of the films increased with increase in substrate temperature. XPS analysis confirms the highly non-stoichiometric nature of the films with dominant occurrence of Ce 4+ (CeO2 ) and subsidiary occurrence of Ce 3+ (Ce2 O3 ).